PENGAPLIKASIAN TEORI KATHERINE KOLCABA PADA KASUS KEPERAWATAN - Depira Elza Nada; Irna Nursanti (Nusantara Hasana Journal, 2024)
The main concept of comfort theory is to assess the taxonomic structure between three comforts associated with four comfort experiences. One of the practical theories that supports the development of humidity both in the development of science and in practice is the comfort theory model developed by Katharine Kolcaba. In Kolcaba's perspective, relief (freedom), ease (calmness), transcendence (happiness) are indicators of providing holistic comfort (Wilson & Kolcaba, 2004). This theory provides a useful framework for improving patient comfort by helping to guide comprehensive intervention for not only physical discomfort, but also emotional or psychological discomfort. According to (Kolcaba, 2001) that patients strive to meet their comfort needs, and a comfort theoretical framework can assist nurses in assessing various comfort needs in "the context in which comfort occurs".